ANALISIS KRIMINOLOGI KULTURAL: PANDANGAN PEMBACA CERITA FIKSI (ALTERNATIVE UNIVERSE) IDOL KPOP BERTEMA BOYS LOVE - Amalia Putri Zalfia Ahmad; Chazizah Gusnita (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
Alternative Universe (AU) with a boys love theme has become one of the choices for Kpop fans who read AU as a sought-after work of fiction. The unusual theme of depicting romantic relationships between males is certainly very taboo and not accepted within societal norms. Nevertheless, fans who read consider that fictional works with this theme to be commonplace in fictional stories that are not real. This research will analyze the form of normalization of sexual deviation found in the depiction of alternative universe stories with a boys love theme from the perspective of Kpop fans who read these fiction. This research will use a qualitative method in a descriptive form. This study will involve preliminary observations of twenty-two readers and will take three samples for further information. This research shows that readers justify the boys love theme in an alternative universe because this theme is only present in fictional works and does not occur in the real world, allowing readers or authors to rationalize the deviations in such fiction.